Agaricomyceteous fungi new to district Kangra (H.P.) - Devi, Ritu (Mushroom Research, 2018)
An account of eight species of resupinate, non-poroid Agaricomyceteous fungi has been given. The paper is based on the morphological and microscopic features observed in the fungal samples collected from district Kangra of Himachal Pradesh during fungal forays conducted from 2014-2016. All the taxonomically identified spices are new to Kangra district of Himachal Pradesh.